Metal Bioaccumulation in Albino Rat Tissues Treated with Decontaminated Sea Lettuce (Ulva lactuca L.) - Mulyati, Mulyati; Wijayanti, Susy; Islahi, Annisa Nur; Saraswati, Anindyanari Rahma Sriyekti; Hasnadewi, Ashfiya Hanif; Setyasari, Safira Ratri Dwi (Universitas Gadjah Mada, 2024)
Ulva lactuca is a macroalgae that contains high nutritional values. The heavy metal contaminants in natural Ulva lactuca needs to be eliminated or decreased using natural agent. The aim of this research was to determine the bioaccumulation of Pb, Cd, Hg, and the impact on liver and gastrointestinal function. Parameters of this research were Hepatosomatic Index (HSI), SGPT levels, SGOT levels, bioaccumulation Pb, Cd, Hg, and histological structure of liver and small intestine. Besides that, the progression of body weight was observed. Twelve female Wistar rats (Rattus norvegicus Berkenhout, 1769) were randomly assigned to three groups: Control, NU (treated with natural Ulva lactuca), and DU (treated with heavy metal decontaminated Ulva lactuca using Averrhoa bilimbi juice).Treatment was carried out orally at a dose of 1000 mg/Kg BW/day for 30 days. Histological structure of rat’s liver and small intestine were prepared after necropsy at the end of this research. Based on results, it can be concluded that there were no significant differences observed in HSI, SGPT, and SGOT levels among the groups. However, there was a tendency for an increase in total bilirubin levels in the decontaminated Ulva lactuca group. Both natural and heavy metal decontaminated Ulva lactuca showed histological damage on liver and small intestine. Bioaccumulation of Cd and Hg in the liver and gastrointestinal tract of rats after consuming decontaminated Ulva lactuca was lower than the natural Ulva lactuca group, but need more observations.